Evaluation of Cardiometabolic Parameters among Obese Women Using Oral Contraceptives - Ferreira, Júnia Raquel Dutra; Aleluia, Milena Magalhães; Figueiredo, Camylla Vilas Boas; Vieira, Larissa Castro de Lima; Santiago, Rayra Pereira; da Guarda, Caroline Conceição; Barbosa, Cynara Gomes; Oliveira, Ricardo Riccio; Adorno, Elisângela Vitória; Gonçalves, Marilda de Souza (Frontiers in Endocrinology, 2017)
Background: Combined oral contraceptive (COC) use has been associated with an unfavorable impact on carbohydrate and lipid metabolism in diverse populations of normal-weight and obese women. The present study aimed to evaluate the cardiometabolic and inflammatory profiles of women in northeastern Brazil with respect to COC use and obesity. Methods: We performed a cross-sectional study to verify cardiovascular parameters, including blood pressure, fasting serum glucose, lipid and inflammatory profile, in a population of women aged 15-45 years, considering obesity and COC use. Our sample consisted of 591 women, 481 women who were COC users and 110 age-matched women who were COC non-users, classified as obese and non-obese according to BMI. Results: COC use and obesity were associated with increased systolic (p ≤0.001) and diastolic blood pressure (p =0.001), blood glucose (p ≤0.001), total cholesterol (p =0.008), low density lipoprotein cholesterol (p ≤0.001), very low density lipoprotein cholesterol (p ≤0.001), triglycerides (p ≤0.001), ferritin (p =0.006), C-reactive protein (CRP)(p ≤0.001) and nitric oxide metabolites (p ≤0.001), as well as decreased high density lipoprotein cholesterol (HDL-c) (p ≤0.001) in comparison to controls. CRP and HDL-c levels in obese COC users were determined to be outside reference range values. The odds of having lower levels of HDL-c and elevated CRP increased among obese COC users. COC use was independently associated with low levels of HDL-c, especially second-generation progestins (p <0.001; OR=8.976; 95% CI 2.786-28.914). Conclusion: Obesity and COC use were associated with alterations in lipid and inflammatory cardiometabolic parameters, particularly increased CRP levels and decreased HDL-c, which are considered markers of cardiovascular disease risk. Given the need to prevent unintended pregnancy among obese women, together with weight loss counseling, it is important to evaluate the most effective and safest contraceptive methods to avoid the potential risk of developing cardiovascular disease.